Mother Goose's Guide to Scrapbooking Your Baby : Creating Fabulous Projects & Pages with Classic Drawings & Cherished Rhymes - Arquette, Kerry and Zocchi, Andrea; Edited by D' Agostino Darlene (New York Lark Books, 2007)
Gathers together several classic illustrations, rhymes and scrapbook art with different layouts.
Include Color Illustration, Bibliography and Index
Keywords: Nursery rhymes in art -- Photograph albums -- Mother Goose